PENGEMBANGAN MODUL MATEMATIKA UNTUK PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) PADA MATERI POKOK PERSAMAAN GARIS LURUS KELAS VIII SMP - Khayati, Fitrotul; Sujadi, Imam; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Absrtact:The objectives of this research were to investigate: (1) how to develop of Mathematics module development for problem-based learning on the topic of discussion of  Linear Equation of Straight Line for Grade VIII of Junior Secondary School; and (2) the effectiveness of result of Mathematics module development for problem-based learning on the topic of discussion of Linear Equation of Straight Line for Grade VIII of Junior Secondary School. This research consisted of two phases. The first phase was the phase for development and stipulation of a module as a product of research and development. It included preliminary study, module development, module validation, focus group discussion, product testing, and revision. The second phase was the phase of module effectiveness testing with the quasi experimental research with the factorial design of 2x1. The population of research was the students in Grade VIII of Junior Secondary Schools in Yogyakarta City. Sample consisted of students of SMP N 5 Yogyakarta and SMP N 2 Yogyakarta.  The data of research were gathered through observation, unstructured interview, questionnaire, and test of learning result. They were then analyzed by using the descriptive quantitative analysis.  Based on the result of the analysis, we can conclude that: 1) development of Mathematics module for problem-based learning on the topic of discussion of Linear Equation of Straight Line for Grade VIII of Junior Secondary School includes preliminary study, module drafting, module validation, module revision I,focus group discussion, module revision II, initial field testing, module revision III, field testing or module effectiveness testing, module revision IV (Finalizing the final product). The result of development in this research was Mathematics module for problem-based learning on the topic of discussion of Equation of Straight Line for Grade VIII of Junior Secondary School. 2) The result of module effectiveness testing shows that Mathematics module for problem-based learning on the topic of discussion of Linear Equation of Straight Line for Grade VIII of Junior Secondary School is proven to be effective.Keywords: Development, Mathematics Module, Problem-based learning